Stereoselective Synthesis of Fluoroalkanes via FLP Mediated Monoselective C─F Activation of Geminal Difluoroalkanes - Dániel Csókás; Bivas Mondal; Miloš Đokić; Richa Gupta; Beatrice J. Y. Lee; Rowan D. Young (Advanced Science, 2023)
Abstract A method of desymmetrization of geminal difluoroalkanes using frustrated Lewis pair (FLP) mediated monoselective C–F activation where a chiral sulfide is the Lewis base component is reported. The stereoselective reaction provides generally high yields of diastereomeric sulfonium salts with dr of up to 95:5. The distribution of diastereomers is found to be thermodynamically controlled via facile sulfide exchange. The use of enantiopure chiral sulfides allows for high stereospecificity in nucleophilic substitution reactions and the formation of stereoenriched products.